Selonsertib Alleviates the Progression of Rat Osteoarthritis: An in vitro and in vivo Study - Yan, Jiyuan; Zhang, Yingchi; Sheng, Gaohong; Ni, Bowei; Xiao, Yifan; Wang, Shanxi; Wang, Tianqi; Ma, Yongzhuang; Wang, Huaixi; Wu, Hua; Tu, Chang (Frontiers in Pharmacology, 2021)
Osteoarthritis (OA) is a prevalent degenerative joint disease. Its development is highly associated with inflammatory response and apoptosis in chondrocytes. Selonsertib (Ser), the inhibitor of Apoptosis Signal-regulated kinase-1 (ASK1), has exhibited multiple therapeutic effects in several diseases. However, the exact role of Ser in OA remains unclear. Herein, we investigated the anti-arthritic effects as well as the potential mechanism of Ser on rat OA. Our results showed that Ser could markedly prevent the IL-1β-induced inflammatory reaction, cartilage degradation and cell apoptosis in rat chondrocytes. Meanwhile, the ASK1/P38/JNK and NFκB pathways were involved in the protective roles of Ser. Furthermore, intra-articular injection of Ser could significantly alleviate the surgery induced cartilage damage in rat OA model. In conclusion, our work provided insights into the therapeutic potential of Ser in OA, indicating that Ser might serve as a new avenue in OA treatment.